BRAF Landscape and Its Implications among Patients with Pediatric Low-Grade Gliomas: A Comprehensive Review of the Literature - Fouda, Mohammed A. (Journal of Pediatric Neurology, 2023)
Low-grade gliomas are the most common intracranial tumor in the pediatric population. Pediatric low-grade gliomas represent a heterogeneous group of tumors. Genetic alterations that result in upregulation of the MAPK/ERK pathway represent most of the genetic landscape of pediatric low-grade gliomas. BRAF-V600E mutant pediatric low-grade gliomas may represent a unique and aggressive subset of tumors that require targeted therapy especially if gross total resection is not feasible. Many patients with pediatric low-grade gliomas have demonstrated successful clinical and radiological responses to BRAF and/or MEK inhibitors. Given the high proportion of patients who fail to respond to the current standard chemotherapy and radiotherapy, these targeted therapies should be considered in future trials and further investigations. In this review of the literature, we summarize the molecular status of BRAF alterations among patients with pediatric low-grade gliomas and provide an update on previous and current BRAF and MEK inhibitors clinical trials.
Keywords: pediatric; low-grade glioma; BRAF; BRAF inhibitors; MEK inhibitors